Diversidade genética em coqueiro-gigante (Cocos nucifera L.) por meio de marcadores microssatélites e características morfoagronômicas - Loiola, Carina Mendes (Universidade Federal Rural do Semi-Árido, 2014)
The tall coconut palm is about 70% of the coconut farm in Brazil. Nonetheless the information about the genetic variability existing in Brazilian populations and their genetic relationships are still incipient. Microsatellite markers or SSR (Simple Sequence Repeats) and morphological markers are the techniques most suitable for studies of genetic diversity. Thus, knowledge of the variability and genetic structure in the giant coconut palm, it is necessary to direct the activities of conservation and use of germplasm in breeding programs of this species. The objectives of this study were: 1) to analyze the distribution of the genetic variability of the original population of Tall-Brazil-Praia-Forte ( GBrPF - PO), located on the north coast of Bahia, and four coming accesses this population; 2) levels of diversity and genetic relationships between two accesses tall coconut palm collected in Brazil and introduced seven accessions of different geographical regions, conserved in Banco Internacional de Coco for Latin America and the Caribbean (ICG - LAC). The accessions were analyzed using 25 SSR primers specific morphological descriptors and 16 of the list of IPGRI, 1995. Accesses tall- Brazil-Praia-Forte (GBrPF) are conserved in physical bases in Ceará (GBrPF-CE), Pará (GBrPF-PA ) and ICG - LAC, the latter two physical bases in Sergipe: one in the experimental field of the Betume in the city of Neópolis (GBrPF-CEB) and the other in the experimental field Itaporanga in the municipality of Itaporanga d'Ajuda (GBrPF-CEI) . The other accesses greens: tall-do-Brazil-Merepe (GBrMe), collected in the coastal Northeast, tall-Malaysia (GML), tall-Vanuatu (GVT), tall-West African (GOA), tall-Polynesia (GPY), tall-Rennel (GRL), tall-Tonga (GTG) and tall-Rotuma (GRT) introduced in different geographic regions of the world, too are conserved in the ICG - LAC in the experimental field of the Betume. Three studies from this research project will be presented. In the first study, we found 18 polymorphic primers, 91 alelos, with a mean of 5.05 alleles/locus. Genotypic indices indicate greater genetic variability of access GBrPF-PA, GBrPF-CE and GBrPF-CEB, the analysis of gene structure identified an allele sharing and access of the population, suggesting that accesses listed represent the genetic structure of the original population. The grouping (UPGMA) showed the formation of 14 groups, with the GBrPF-CEB and GBrPF-PA showed greater similarity to the original population accesses. In the second study, for the study of genetic relationships among accessions of tall coconut palm, 19 primers were polymorphic, detecting 125 alleles, with an average of 6.57 alleles/locus. Genotypic indices indicate greater genetic variability among accessions of coconut - derived giant introduced the Pacific region. The analysis of gene structure led to the formation of five groups and accessions collected in Brazil showed genetic relationship with the African access and the emergence of ecotypes giant coconut palm in Brazil. Cluster analysis by the Nearest Neighbor method formed two main groups. In group I, the accessions were grouped into three subgroups: Ia (GTG, GRT and GPY), Ib (GRL and GVT) and Ic (GML). In group II, the accessions were separated into two subgroups: IIa (GOA) and IIb (GBrMe, GBrPF),indicating that the genetic relationships of the accessions are based on ecogeographic regions. In the third work, the study of genetic diversity through morphological markers using techniques of univariate and multivariate genetic variability was observed among genotypes. The results of principal component analysis, obtained from 16 morphological characters shows that three components were needed, that the variance explained by them reached a minimum of 80% and the selection of six characters with the highest contribution to the study of diversity. UPGMA was formed by five groups. Group I meets the GVT and GML access; group II with GPY, GTG and GBrPF; group III and IV each with one access, GRT and GOA, respectively, while group V with GBrMe and GRL. Groups showed an inconsistency with respect to the origins of the accessions, probably due to the quantitative nature of those characteristics that are controlled by many genes, being affected by environmental factors. Diversity and genetic structure evaluations demonstrate the variability and genetic relations in giant coconut palm. These results will guide decisions about the activities of conservation and use of coconut germplasm in the country
Genetic diversity inthe giant coconut palm(Cocos nuciferaL.) using microsatellitemarkers andagronomictraits
Keywords: Cocos nucifera L.; Recursos genéticos; Relações genéticas; Diversidade genética; Marcadores Moleculares e Morfoagronômicos; Técnicas multivariadas; Cocos nucifera L.; Genetic Resources; Genetic Relationship; Genetic diversity; Markers molecular and morphological; Multivariate techniques; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA